How programs in prisons are challenging the who, where, how, and what of theological education - Jobe, Sarah C. (Teaching theology and religion, 2019)
This paper claims that programs in prisons are challenging the very who, where, how, and what of theological education. The author draws on research from the fields of pedagogy and prison studies, nearly a decade of experience teaching master's level seminary-style classes in prison, and the findings of a two-year cohort of prison educators convened by the Association of Theological Schools for their Educational Models and Practices Project. Addressing displacement as a learning strategy, classroom diversity, the use of student experience, narrative grading strategies, and classroom ritual, the author shows how the teaching strategies emerging from prison classrooms provide vibrant models for the theological academy at large.